Probiotic Characteristics of Enterocin-Producing Enterococci Isolated from Traditional Turkish Cheeses - Kankaya, DA (Journal of the Hellenic Veterinary Medical Society, 2025)
This study aimed to evaluate the probiotic properties of the bacteriocin-producing strains E. faecium DP8.3, E. faecium DP9.3 and E. mundtii DP35.1. All strains were found to survive at pH 3.0 and maintained their viability in the presence of 0.4% phenol and 100 ppm lysozyme. In simulated gastric juice adjusted to pH 3.0, the viable cell counts for E. faecium DP8.3, DP9.3, and E. mundtii DP35.1 were 8.96±0.01, 8.37±0.00, and 8.63±0.21, respectively. The bacteriocin-producing strains were capable of surviving at bile salt concentrations of 0.3%, 0.5%, and 1%. Additionally, these strains were able to grow in the presence of taurocholic acid, glycocholic acid, taurodeoxylic acid sodium salts, and glycodeoxycholic acid sodium salts. The strains exhibited high hydrophobicity, autoaggregation, and coaggregation abilities. According to the results, these bacteriocin-producing strains possess probiotic properties, suggesting their potential use as protective probiotic cultures in food production. Further studies, including in vivo studies and food trials, is required to assess the potential of these strains as protective probiotic cultures in the food industry.